Carotenoides y actividad antioxidante - Vargas Villasis, Kerwin Manuel (2022)
Carotenoids are essential natural pigments for photoprotection against excess light in plants, although they are best known for being responsible for the yellow, orange and red color of fruits. These are mainly synthesized de new by photosynthetic organisms and some bacteria, yeasts and fungi, and animal organisms must ingest them through the diet. To date there have been several reports of the benefits of carotenoids in health maintenance, and most of these approaches are associated with their provitamin a biological activity. However, carotenoids are much more than just pigments, they are also powerful antioxidants. This due to the composition of its structure that is formed by double bonds, which can interact with free radicals and prevent them from causing damage to cellular and tissue components, almost all carotenoids can act as antioxidants. For these reasons, several investigations related to the identification, quantification and antioxidant activity/capacity of the antioxidants of these compounds have been carried out. Antioxidant activity can be monitored using a variety of assays involving different mechanisms, such as hydrogen atom transfer, single electron transfer, reducing power, and metal chelation. Likewise, there are also biological methods at the molecular level and system models, however chemical methods provide ease of extraction, in this sense the adequate selection of the method or the combination of methods is of the utmost importance for an evaluation of the valid antioxidant activity and determine the potential of the antioxidant as a food preservative or health promoting agent.